2001
DOI: 10.1002/nur.1042
|View full text |Cite
|
Sign up to set email alerts
|

Chronic venous insufficiency in persons with a history of injection drug use¶

Abstract: Persons with a history of injection drug use have many risk factors for the development of chronic venous insufficiency (CVI), yet this phenomenon has not been studied systematically in this population. Persons (N = 204) with a history of injection drug use who were in enrolled in a treatment center were examined for clinical manifestations of CVI. The CVI clinical classification was graded on a 7-point scale for each leg. Most participants (n = 179, 87.7%) exhibited clinical evidence of CVI. Significant predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 38 publications
1
52
0
2
Order By: Relevance
“…[1][2][3] Some IRIDs (e.g. endocarditis, tetanus) are extremely serious and require urgent medical attention; some (abscesses, cellulitis) are easily treated, but potentially life-threatening, while others (hives, swelling) are minor but common conditions.…”
mentioning
confidence: 99%
“…[1][2][3] Some IRIDs (e.g. endocarditis, tetanus) are extremely serious and require urgent medical attention; some (abscesses, cellulitis) are easily treated, but potentially life-threatening, while others (hives, swelling) are minor but common conditions.…”
mentioning
confidence: 99%
“…This classification has seven categories: Class 0 (no visible or palpable sign of venous disease), Class 1 (telangiectasis, reticular veins, malleolar flare), Class 2 (varicose veins), Class 3 (edema without skin changes), Class 4 (skin changes ascribed to venous disease such as increased pigmentation, venous eczema, and lipodermatosclerosis), Class 5 (skin changes as defined previously with healed ulceration), and Class 6 (skin changes as defined previously with active ulceration) (Porter et al, 1996). The authors' previous work assessed the reliability of the clinical classification on 20 randomly chosen participants; the result was perfect (Kappa ϭ 1.0) (Pieper & Templin, 2001). Researchers who used the clinical classification with objective venous testing concluded that it accurately identified categories of chronic venous disease (Kistner, Eklof, & Masuda, 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research on persons who had a history of IDU showed that injection in the groin, legs, and feet rather than injection in other parts of the body was primarily responsible for increased CVI risk (Pieper & Templin, 2001). In the current sample, a small number, 5 persons, injected drugs only in the arms or upper parts of the body.…”
Section: Ankle Mobility and Chronic Venous Insufficiencymentioning
confidence: 94%
“…Repeated infections also lead to damage to lymphatic vessels, which impairs lymphatic drainage. Chronic lower extremity edema often results from the combination of lymphatic obstruction and venous insufficiency [4,20,21].…”
Section: Vascular Complicationsmentioning
confidence: 99%